Hubungan Kegiatan Pentas Seni Dengan Rasa Percaya Diri Anak Usia Dini - D, Deardjati; Ratnasih, Teti; Nurdiansah, Nano (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Performing arts is one of the activities that can provide first-hand experience for early childhood in expressing themselves, developing courage, as well as training a sense of self-confidence. This study aims to know the relationship between performing arts activities and early childhood confidence. The research method used was correlational quantitative with total sampling technique. Study subjects a total of 15 children of group B RA Al-Mukhlisin 2. Data were collected through observation, interviews, and documentation, then analyzed using product moment correlation test. The results of the study showed that art penta activities were in the good category with an average score of 77, while children’s self-confidence was in the excellent category with a mean score of 89. The results of correlation analysis obtained a value of r = 0.746 with a significance of 0.001, which means that there was a significant relationship between the activities of children and children’s sense of pentas. religion. The coefficient of determination shows that art scenery contributes as much as 55.6% to children’s sense of self-confidence, while 44.4% is influenced by other factors. Thus, it can be concluded that performing arts activities play an important role in boosting early childhood self-confidence.